2020
DOI: 10.1590/fst.42918
|View full text |Cite
|
Sign up to set email alerts
|

Extract of Ellagitannins starting with Strawberries (Fragaria sp.) and Blackberries (Rubus sp.)

Abstract: Characterize the content of phytochemical compounds present in samples of extracts of strawberry (Fragaria sp.) and blackberry (Rubus sp.). The extraction of said compounds was carried out with solutions of polar solvents, such as acetone, ethanol and methanol, using an experimental design with three factors: state of maturity, resting time and temperature. The characterization of these fruits is the beginning of the utilization mainly of ellagitannins to produce ellagic acid. Total phytochemical content was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Ellagitannins (ETs) are secondary plant metabolites belonging to the group of hydrolysable tannins (Feldman et al 2003;Dai and Mumper 2010). They exhibit beneficial health properties, including antioxidant, antibacterial, antiviral, and anti-inflammatory activity (Sangiovanni et al 2013;Kahkonen et al 2012;Larrosa et al 2010;Puljula et al 2020;Marquez -Lopez et al 2020). The health-promoting activity of ETs has been demonstrated both in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Ellagitannins (ETs) are secondary plant metabolites belonging to the group of hydrolysable tannins (Feldman et al 2003;Dai and Mumper 2010). They exhibit beneficial health properties, including antioxidant, antibacterial, antiviral, and anti-inflammatory activity (Sangiovanni et al 2013;Kahkonen et al 2012;Larrosa et al 2010;Puljula et al 2020;Marquez -Lopez et al 2020). The health-promoting activity of ETs has been demonstrated both in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this, TPC of 80% methanol extracts was the highest (33.94 mg GAE g -1 extract) among other solvent extracts of strawberry. Márquez-López et al (2020) reported that methanol extracts of strawberries contained higher total phenolic compounds than ethanol extracts. It is explained by the higher polarity of methanol and the higher solubility of phenolic compounds as the polarity increases, because phenols in extracts are largely related to the polarity of the solvents used (Márquez-López et al, 2020).…”
Section: Total Phenolic Contentmentioning
confidence: 99%
“…Also, they are rich in anthocyanins, which are responsible for the red color and are powerful antioxidants. Many studies have studied anthocyanin content and antioxidant potential in strawberry (De Souza et al, 2014;Mandave et al, 2014;Chaves et al, 2017;Márquez-López et al, 2020), raspberry (Pantelidis et al, 2007;Çekiç and Özgen, 2010;Chen et al, 2013a;Dragišic Maksimovic et al, 2013;De Souza et al, 2014), sour cherry (Kim et al, 2005;Piccolella et al, 2008;Khoo et al, 2011;Kopjar et al, 2014) and cornelian cherry (Pantelidis et al, 2007;Yilmaz et al, 2009;Hassanpour et al, 2011;Celep et al, 2012;Moldovan et al, 2016). Potential health effects of these fruits associated with anthocyanin were studied in the literature (Ferretti et al, 2010;Chen et al, 2013b;Khoo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have molecular weights between 500 and 30,000 Da and are present in each and every plant food and beverage 2 . These compounds are found in plant parts, for example, in roots, stems, bark, trunk, leaves, flowers, fruits, and seeds, which are an indispensible part of human diet 3 . Moreover, these metabolites occur widely in foodstuffs such as tea, strawberries, blackberries, grapes, mangoes, cashew nuts, hazelnuts, and walnuts and can precipitate proteins, minerals, starch, and cellulose from various solutions 4 .…”
Section: Introductionmentioning
confidence: 99%